An Analysis of Non-Observance Maxims and The Implicature in The Podcast Youtube Channel The Leonardo's "Face To Face With Onadio Leonardo - Vior" - Veronika Simbolon (JEES: Journal of Education and Educational Sciences, 2024)
This research is Analysis of Non-Observance Maxims and The Implicature In The Podcast On The Leonardo's youtube Channel "Face to Face with Onadio Leonardo - Vior" which is 41:10 minutes long. This research uses Qualitative descriptive method, data collection technique by watching podcasts then analyzing the non-observant maxims in the conversation and then writing them down.The data source in this research is conversations in podcasts on channels Youtube “Face to Face with Onadio Leonardo - Vior”. Analysis results show podcast reveals six non-observance maxims, including flouting relevance 4, violating maxim 1, and opting out maxim 1. The most common non-observance maxim is flouting relevance, consisting of three statements. This investigation helps determine which maxims were broken in the podcast.